Pentingnya Branding Pada Kemasan Dan Strategi Pemasaran Dalam Meningkatkan Daya Saing Pada Umkm Desa Ciparay - Rahayu, Dede Sri; Dahlia, Eli (CV. Global Cendekia Inti, 2024)
Majalengka Regency, as a government city, is participating in the competition to improve the standard of living of the people. One area in Majalengka Regency that has quite a lot of MSMEs is Ciparay Village, Leuwimunding District. In this area there are quite a lot of micro, small and medium enterprises (MSMEs) with various types of business, such as craft and snack businesses. Brand is the most important strategic asset for business actors which also needs to be paid attention to by MSMEs in Ciparay Village, Leuwimunding District , which is able to create value or benefits for customers and companies. The increasing number of MSMEs in Majalengka Regency requires that MSMEs in Ciparay Village, Leuwimunding District also need to increase the competitiveness of their products. One way that entrepreneurs can do this is by branding or building a brand. Packaging is closely related to branding itself . In packaging design, it is not just about designing, it requires ideas that are able to convey the advantages of a brand or product so that the appearance of the design is able to sell and the appearance of the packaging is also important. must be attractive and pleasing to the eye to attract consumers. This community service activity is aimed at providing knowledge and motivating MSMEs in Ciparay Village, Leuwimunding District, Majalengka Regency to be more creative and innovative in marketing their products. The type of activity that will be carried out is in the form of a workshop. The method used in this activity are presentation and discussion methods. The results of this activitiy are the community service carried out at Ciparay Village MSMEs, Leuwimunding District, Majalengka Regency went well and smoothly where participants took part in the activities with enthusiasm and the material presented can be received, digested and understood participants well.